Evaluation system of coastal wetland ecological vulnerability under the synergetic influence of land and sea: A case study in the Yellow River Delta, China. (December 2020) - Shi, Honghua; Lu, Jingfang; Zheng, Wei; Sun, Jingkuan; Li, Jie; Guo, Zhen; Huang, Jiantao; Yu, Shuting; Yin, Liting; Wang, Yongzhi; Ma, Yuxian; Ding, Dewen
Abstract: A comprehensive evaluation system and model of Coastal Wetland Ecological Vulnerability (CWEV) was constructed and applied to reveal spatial heterogeneity of the ecological vulnerability of the Yellow River Delta Wetland (YRDW). The results showed that the score of the ecological vulnerability (EVS) of the YRDW was 0.49, which was generally at a medium vulnerability level. The wetland area of high vulnerability was up to 943km 2, accounting for 35.2% of the total area, followed by the medium vulnerable area with an area of 750km 2, accounting for 28.1% of the total area. From the coastline perpendicularly to the land, the "seaward" gradient effect gradually decreased, the vulnerability-increasing "hydrologic connectivity" effect increased with the distance from the river channel, and the "land source influence" effect gradually decayed along with the vulnerability of population and economy gathering areas. Graphical abstract: Unlabelled Image Highlights: A comprehensive evaluation metric system and model of coastal wetland ecological vulnerability (CWEV) was constructed. The spatial heterogeneity of the CWEV was revealed. The CWEV was mainly affected by land source interference, marine interference, and river network distribution. The CWEV showed a "seaward" gradient effect, a "hydrologic connectivity" effect and a "land influence" effect.